Perancangan User Interface Website Surakartea Sebagai Media Promosi Dan Branding Kedai Teh Surakartea - Wicaksono, Arif; Syahran, Unggul Aida (Universitas Pelita Bangsa, 2025)
With the proliferation of coffee shops in Indonesia, especially in Surakarta, there is the Surakartea tea shop, which offers various processed tea products for the people of the city of Surakarta. In its efforts to introduce tea products and their benefits, Surakartea has used word-of-mouth promotion and social media as its main promotional media; however, over time, social media has limited features and coverage. In the period 2019 to 2023, website promotion media experienced an increase in the need for website existence. Data shows that the number of internet users in Indonesia continues to increase, and there is a shift in consumption from traditional sales patterns to website-based digital sales systems. In this research, the researcher created a design to design a website user interface (UI) for the Surakartea tea shop brand using the design thinking method. With the Surakartea website prototype user interface, it is hoped that the public can become a reference for the Surakartea coffee shop in developing its official website in the future so that it will be easy to promote products and other important information to the general public.